THE WESTERN PRAGMATISM PHILOSOPHY BASED ON KALÂM JADÎD’S PERSPECTIVE - Muslih, Muhammad Kholid; Zarkasyi, Amal Fathullah; Hidayat, Muhammad Sofian (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This article examines the philosophy of Western pragmatism since pragmatism is considered to be a real threat to human civilisation. It happens because pragmatism, as a philosophy, makes empirical facts and usefulness as the basis of everything. Thus, it fosters a sceptical attitude towards everything, doing things based on certain benefits, and ignoring norms as well as religious values. This study is a literature study since it examines various sources (books and scientific articles) analysed with a socio-historical approach with Kalâm jadîd science as the basis. The study focuses on the critical analysis on the concepts of knowledge, truth, morals and religion of the philosophy of pragmatism. This study shows that the concept of the philosophy of pragmatism is extremely contrary to Islamic values and teachings. Firstly, pragmatism has its own concept of truth, where empiricism and coherence of ideas and reality determine the value of a truth. Secondly, knowledge will be considered relevant as a scientific discipline if it is able to have a direct impact on and value or benefits for human life. Thirdly, religion and morals are realised as actions done according to human will.